Avaliação do perfil lipídico entre indivíduos com hepatite C - Nogueira, Camila Tita [UNESP]; Urbaczek, Ana Carolina [UNESP]; Falcoski, Thaís Oliveira Rodrigues [UNESP]; Isabel, Thaís Ferreira [UNESP]; Graminha, Márcia Aparecida Silva [UNESP]; Costa, Paulo Inácio da [UNESP] (My University, 2012)
Metabolic profiles correlate with hepatitis C virus (HCV) infection and are prognostic for the viral response. However, little is known about the association between lipid profiles and viral load in chronic patients carrying HCV genotypes 1, 2 and 3. The aim of this study was to investigate the influence of the viremia and viral genotype on lipid metabolism by observing the variations in serum lipoprotein and apolipoprotein B, to assess whether HCV predisposes individuals to lipid imbalance and favors the appearance of vascular complications. A sample group of 150 chronic HCV patients with viral genotypes 1, 2 or 3 and a control group of 20 healthy adults (10 men and 10 women), all aged from 20 to 50 years were studied. The serum lipid profile of the chronic patients was analyzed and compared to that of the control group. The high-density lipoprotein (HDL), very low-density lipoprotein (VLDL) and triglyceride levels of the sample group were lower than those of the control group, while the low-density lipoprotein (LDL) and apolipoprotein B levels of the patients were higher. These differences were more significant in patients carrying genotype 3a. There was a positive correlation between the viremia and the changes in apolipoprotein B levels in patients carrying genotype 1b. It was inferred that the risk of developing vascular complications raised in HCV patients. As 90% of LDL protein is composed of apolipoprotein B, the plasmatic concentration of the latter indicates the number of potentially atherogenic particles. Therefore, the lipid profile monitoring may aid in the diagnosis of hepatic infection severity and equally act as a good prognostic marker.
Evaluation of the lipid profile between individuals with hepatitis C
Keywords: Genotypes; Hepatitis C vírus; Lipoproteins; Viremia; apolipoprotein B; high density lipoprotein; low density lipoprotein; triacylglycerol; very low density lipoprotein; adult; cholesterol blood level; controlled study; disease predisposition; enzyme blood level; evaluation; female; genetic association; genotype; hepatitis C; human; lipid analysis; lipid metabolism; lipoprotein blood level; major clinical study; male; risk assessment; triacylglycerol blood level; vascular disease; virus gene; virus load